2008
DOI: 10.1007/s00432-008-0445-8
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of the DYX1C1 gene and its application as a cancer biomarker

Abstract: Our results indicated that alternatively spliced transcript variants of the DYX1C1 gene could be used as cancer biomarkers to detect colorectal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
10
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 24 publications
5
10
1
Order By: Relevance
“…This result is concordant with a previous report on the expression of the DYX1C1 gene (Kim et al, 2009). DYX1C1 has a role in the migration of neocortical neurons and, more specifi- Fig.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…This result is concordant with a previous report on the expression of the DYX1C1 gene (Kim et al, 2009). DYX1C1 has a role in the migration of neocortical neurons and, more specifi- Fig.…”
Section: Resultssupporting
confidence: 93%
“…The four alternative spliced forms (V1-1, V1-2, V1-3, and V1-4) resulted in DYX1C1 either acquiring novel exons or losing original exons. The PCR products of V1-1 and V1-2 showed only a subtle difference in size, though V1-1 contains an extra exon compared to V1-2 (Kim et al, 2009). We also confirmed these alternative forms by sequencing them.…”
Section: Resultssupporting
confidence: 61%
See 1 more Smart Citation
“…58,59 Apart from its clear role in neuronal migration, several alternatively spliced transcript variants of DYX1C1 appear to be biomarkers for colorectal cancer. 60 In addition, through one of its tetratricopeptide repeat domains, the DYX1C1 protein functions as a cochaperone by interacting with HSP70 (heat shock protein 70) and HSP90 (heat shock protein 90) proteins in breast cancer cells. 61 Finally, in hippocampal neurons, DYX1C1 interacts with both the nuclear and cytoplasmic estrogen receptors a (ESR1) and b (ESR2) 62 (see below).…”
Section: 3mentioning
confidence: 99%
“…The expression pattern of the transcripts is different between normal and cancer tissues. Thus, it was suggested that the alternatively spliced transcript variants of DYX1C1 gene could be used as a cancer biomarker (Kim et al 2009). In addition, the Choroideremia (CHM) gene has two transcript variants, CHM isoform a and b. LTR12C element existing in the gene confer an alternative splicing site on the gene which result in CHM isoform b.…”
mentioning
confidence: 99%